'Scan-negative' cauda equina syndrome: Evidence of functional disorder from a prospective case series. (April 2015) - Hoeritzauer, Ingrid; Doherty, Carolynne M.; Thomson, Stacey; Kee, Rachel; Carson, Alan; Eames, Niall; Stone, Jon
Abstract In the first prospective comparison of 'scan-negative' (n = 11) and 'scan-positive' (n = 7) patients with cauda equina syndrome (CES) we found that Hoover's sign of functional leg weakness but not routine clinical features differentiated the two groups (p < 0.02). This offers a new direction of study in this area, although magnetic resonance imaging is still required for all patients with possible CES.